(untitled) (Tanzania Journal for Population studies and Development, 2018)
Research on market orientation has produced empirical evidence of the positive influence of market orientation on various performance measures of business firms. Despite this evidence, firms have been observed to implement market orientation in varied degrees. Literature on factors influencing implementation of market orientation is scanty, which could arguably explain the lethargy in the implementation of this strategic orientation. This article examines the influence of market-based reward system on market orientation of service firms in Tanzania. Using data from 178 service firms in Tanzania, the article concludes that reward systems positively influence market orientation of service firms in Tanzania. It recommends that organizations to use market-based reward systems to evaluate and compensate employees so as to stimulate market orientation culture and improve firm performance.